Scientometric analysis of the scientific research on the evaluation of the implementation of e-learning in the period 2000-2015 - Diana Marcela Cardona-Román; Jenny Marcela Sánchez-Torres (Pontificia Universidad Católica del Perú, 2017)
A documental review to provide an overview about the evaluation of implementation of e-learning beginning with the exploration in Scopus and Web of Science (WoS) from 2000 to 2015 has been carried out. It was used a methodology for analyzing scientometric with five stages: i) Recovery, ii) Migration, iii) Analysis, iv) Display and v) Interpretation. A set of 1147 records were analyzed, and, it was found that countries with the greatest contribution to research in e-learning were: the United States, Spain, UK, Australia and Germany. The study shown a range of topics related to e-learning and knowledge in different areas, but also a lack of worldwide research and Latin American authors were identified. Finally, this work will allow researchers to identify trends over the last fifteen years.